Transition from Conventional Curriculum to Problem-Based Learning at Faculty Of Medicine, Syiah Kuala University: Lessons Learned - Rosaria Indah (Universitas Syiah Kuala, 2010)
Abstract. In 2006 Faculty of Medicine Syiah Kuala University introduced an integrated, spiral curriculum, using problem-based learning (PBL) approach with a number of innovative features. The faculty of medicine now had four years experience of the curriculum. This paper describes the changes that have taken place in the curriculum over the four years. Evidence from internal and external reviews are used to identify the lesson learned from implementing the curriculum. ( JKS 2010;2:117-122)Keywords:problem-basedlearning (PBL), curriculum.